The Global Status and Trends of Enteropeptidase: A Bibliometric Study - Yang, Xiaoli; Yin, Hua; Peng, Lisi; Zhang, Deyu; Li, Keliang; Cui, Fang; Xia, Chuanchao; Huang, Haojie; Li, Zhaoshen (Frontiers in Medicine, 2022)
ABSTRACT Background: Enteropeptidase (EP) is a type II transmembrane serine protease and a physiological activator of trypsinogen. Extensive studies related to EP have been conducted to date. However, no bibliometric analysis has systematically investigated this theme. Our study aimed to visualize the current landscape and frontier trends of scientific achievements on EP, provide an overview of the past 120 years and insights for researchers and clinicians to facilitate future collaborative research and clinical intervention. Methods: Quantitative analysis of publications relating to EP from 1900 to 2020 was interpreted and graphed through the Science Citation Index Expanded of Web of Science Core Collection (limited to SCIE). Microsoft office 2019, GraphPad Prism 8, VOSviewer, and R-bibliometrix were used to conduct the bibliometric analysis. Results: From 1900 to 2020, a total of 1034 publications were retrieved. The USA had the largest number of publications, making the greatest contribution to the topic (n=260, 25.15%). Active collaborations between countries/regions were also enrolled. Grant D and Hermontaylor J were perhaps the most impactful researchers in the landscape of EP. Protein Expression and Purification and the Journal of Biological Chemistry were the most prevalent (79/1034, 7.64%) and cited journals (n=2626), respectively. Using the top 15 citations and co-citations achievements clarified the theoretical basis of the EP research field. Important topics mainly include the structure of EP, the affective factors for activating substrates by EP, EP-related disorders, and inhibitors of EP. Conclusion: Based on the bibliometric analysis, we have gained a comprehensive analysis of the global status and research frontiers of studies investigating EP, which provides some guidance and reference for researchers and clinicians engaged in EP research.